Interphase effect on the effective moisture diffusion in epoxy–SiO2 composites. (July 2022) - Herrmann, A.; Erich, S.J.F.; van der Ven, L.G.J.; Huinink, H.P.; van Driel, W.D.; van Soestbergen, M.; Mavinkurve, A.; De Buyl, F.; Fischer, H.R.; Mol, J.M.C.; Adan, O.C.G.
Abstract: Epoxy Mold Compounds (EMC) are used to protect integrated circuits (IC) from environmental influences, with one of these influences being moisture ingress, causing corrosion. To obtain the needed thermal and mechanical properties EMCs require a high loading of (silica) fillers, introducing a large amount of interface. While silane coupling agents promote good binding, they have shown to introduce an interphase volume that exhibits a faster moisture transport between epoxy and SiO2 in glass fiber filled epoxy. In this work, we investigate if such an interphase volume is also introduced by the filler particles in EMC and if it influences the moisture diffusion coefficient of the composite. We compare moisture uptake measurements performed by dynamic vapor sorption (DVS) with predictions from effective medium theory, as well as with numerical simulations based on micro-CT scans of our samples for a model epoxy system containing different filler levels and commercial EMC samples with two different filler levels. From the measured DVS data, we observe an effective diffusion coefficient, that is higher than predicted for an absence of any interphase for both the EMC and the model system. This suggests that an interphase layer should be present. Graphical abstract: Unlabelled Image Highlights: Both interphase and filler particles impact the effective diffusion coefficient. Interphase diffusion has shown to increase the effective diffusion coefficient. The interphase effect is less pronounced with increasing temperature. The interphase thickness is larger than 100 nm. Faster diffusion along the interphase speeds up moisture diffusion in EMC.